FROM THE HISTORY OF PHYSICS : Mysteries of diamond synthesis at the Institute of High Pressure Physics of the Academy of Sciences of the Soviet Union. (3rd October 2019) - Stishov, S M
Abstract: A history of diamond synthesis at the Institute of High Pressure Physics, Academy of Sciences of the Soviet Union (IHPP), is described based on archival materials. Many details of those events are still unclear. In particular, it is not known what IHPP researcher was the first to see in his apparatus the first diamond synthesized in the USSR. Nor is it entirely clear why the high-pressure group at the Institute of Crystallography, Academy of Sciences of the Soviet Union, which was quite close to success, was ruthlessly liquidated. The history described allows the reader to better understand the organization of science in the USSR that is often idealized nowadays.